2019
DOI: 10.1029/2018wr023806
|View full text |Cite
|
Sign up to set email alerts
|

Improved Assessment of Atmospheric Water Vapor Content in the Himalayan Regions Around the Kullu Valley in India Using Landsat‐8 Data

Abstract: In this study, we present an approach for improved estimation of atmospheric water vapor content (WVC) from Landsat‐8 data. The initial estimates of WVC derived from the split window covariance variance ratio (SWCVR) method are sequentially improved by two exponential models. The first model is designed to apply orographic corrections to the SWCVR estimate using a 1‐arcsec Shuttle Radar Topography Mission digital elevation model based on a scale and bias parameter for the change in elevation. This model is bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…NDVI is a very sensitive indicator to detect changes in vegetation (Bhardwaj et al 2016;Varade and Dikshit 2019). Figure 6 shows the distribution of NDVI for three years in Srinagar city.…”
Section: Assessment Of Ndvi and Ndwimentioning
confidence: 99%
“…NDVI is a very sensitive indicator to detect changes in vegetation (Bhardwaj et al 2016;Varade and Dikshit 2019). Figure 6 shows the distribution of NDVI for three years in Srinagar city.…”
Section: Assessment Of Ndvi and Ndwimentioning
confidence: 99%
“…A rural aerosol and midlatitude winter atmospheric model was considered for the atmospheric correction (Cooley et al, 2002;Cao et al, 2012;Li et al, 2018). The reference snow cover maps were derived by thresholding the normalized NDSI images (Hulley et al, 2015;Varade & Dikshit, 2018), and the thresholds (th NDSI ), shown in Table 1, were selected based on the observation of the histogram of these images (Gascoin et al, 2018(Gascoin et al, , 2019Hall et al, 1987;Varade & Dikshit, 2019a, 2019b. The percentage of snow cover area based on these maps after masking for cloud, layover, and shadow is also shown in Table 1.…”
Section: 1029/2019wr025449mentioning
confidence: 99%
“…The surface types in different regions are different, so the retrieval method obtained by using statistical methods is mainly suitable for local regions. Although the physical method is based on energy balance and has high retrieval accuracy [27,28], it requires many parameters. Due to the insufficient information for remote sensing observation, the number of unknowns is more than the number of equations, which forms an "ill-conditioned" problem.…”
Section: Introductionmentioning
confidence: 99%
“…−WVC r (g/cm 2 )LST and LSE+4BTs(27,29,31,32) LST and LSE+4BTs(28,29,31,32) LST and LSE+4BTs(27,28,31,32) 4BTs(27,29,31,32) 4BTs(28,29,31,32) 4BTs(27,28,31,32) …”
mentioning
confidence: 99%